A problem-solving environment (PSE) for distributed computing. (23rd January 2006) - Kawata, Shigeo; Usami, Hitohide; Hayase, Yoshikazu; Miyahara, Yutaka; Yamada, Motohiro; Fujisaki, Masahide; Numata, Yohji; Nakamura, Shinji; Ohi, Noriyuki; Matsumoto, Masami; Teramoto, Takayuki; Inaba, Masumi; et al.
A problem-solving environment (PSE) for a distributed high-performance computing (HPC) is proposed to help users to work on distributed computer environment. When users access and use distributed computers for scientific computations, the PSE tells users which computers are available and appropriate for their specific application software by using hardware and software informations specified. Then, the users deploy their software on the distributed computer systems. The software, which can be used later or available for other users, is plugged and pooled in the PSE application pool in order to enhance their reusability. The problem-solving process work flow (WF) is also stored in a case-based database (DB) in the PSE and then the case DB can be used to suggest a WF for users to solve their problems. The PSE may open a new flexible HPC environment.